2020
DOI: 10.1016/j.jclinane.2020.110005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical comorbidities, characteristics, and outcomes of mechanically ventilated patients in the State of Michigan with SARS-CoV-2 pneumonia

Abstract: Highlights Retrospective multi-center study of patients with confirmed coronavirus (SARS-CoV-2). Consecutive patients requiring mechanical ventilation from March 10 to April 15, 2020 enrolled. Increased age, hypertension, statin use, increased fluid administration were associated with increased mortality. Need for continuous renal replacement therapy (CRRT), and vasopressor use were associated with increased mortality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 3 publications
0
40
0
1
Order By: Relevance
“…[4][5][6][7][8][9] The data are, however, limited and contradictory with some studies reporting no difference while others showing adverse outcomes in statin users compared with non-users. [10][11][12][13] In the present meta-analysis, we found that statin use was associated with improved clinical outcomes in patients with COVID-19. The benefit was observed even though statin users were more likely to be old and likely to suffer from comorbid conditions, notably, hypertension, diabetes mellitus and ischaemic heart disease, all of which are known to independently increase the risk of adverse outcomes and mortality in COVID-19.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…[4][5][6][7][8][9] The data are, however, limited and contradictory with some studies reporting no difference while others showing adverse outcomes in statin users compared with non-users. [10][11][12][13] In the present meta-analysis, we found that statin use was associated with improved clinical outcomes in patients with COVID-19. The benefit was observed even though statin users were more likely to be old and likely to suffer from comorbid conditions, notably, hypertension, diabetes mellitus and ischaemic heart disease, all of which are known to independently increase the risk of adverse outcomes and mortality in COVID-19.…”
Section: Discussionmentioning
confidence: 48%
“…[4][5][6][7][8][9] On the contrary, other studies showed either no differences in outcomes [10][11][12] or even adverse outcomes in statin users. 13 There exist two metaanalyses in this regard; while one showed that statin use did not improve the in-hospital outcomes, 14 the other reported a 30% reduction in fatal or severe disease. 3 Although the two meta-analyses were conducted at an almost similar time period, the studies included were highly variable.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, 24 eligible observational studies were identified that reported valuable data on in-hospital mortality and/or COVID-19 disease severity, including three studies of patients with diabetes [14] , [15] , [17] . Of these selected studies, 14 provided data on in-hospital mortality [15] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] ( Table 1 )—although one reported only adjusted hazard ratios (HRs) with no crude numbers of deaths in statin users vs non-users and, therefore, could not be included in the meta-analysis (authors were contacted, but did not communicate their results) [26] —while 11 studies reported data on COVID-19 severity (as determined by ICU, IMV; Table 2 ) [18] , [22] , [23] , [27] , [28] , [30] , [31] , [32] , [33] , [34] , [35] . Also, a study by Tan et al [36] collected very few events in a Chinese population (personal communication from the authors), thereby preventing the use of this study in the final analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The included observational studies reporting data on in-hospital mortality are listed in Table 1 [15] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] . Results of the corresponding meta-analysis are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, 44 articles were excluded because of a sample size less than 100, 47 articles were eliminated due to the potential duplicate patients, and two articles were removed because they reported unclear prevalence of asthma in COVID-19 patients (eTable 2). Ultimately, 116 articles (119 studies) 4 , 6 , 7 , 8 , 9 , 10 , 11 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ,…”
Section: Resultsmentioning
confidence: 99%